Class origins, higher education and employment in China during the 21st century. (6th December 2020) - Lin, Yuqi; Chan, Philip Wing Keung
Abstract: The liberal theory of industrialism is one of the chief political theories impacting education. Such a framework associates academic achievement directly with employability and establishes education's dominant position in mediating social mobility. However, Chinese graduates are confronted with the broken promises of higher education, since college credentials are no longer regarded as 'golden tickets' that guarantee decent jobs or high social status. Therefore, this paper establishes a critical framework for analysing the liberal theory of industrialism. By referencing to empirical research, the current study provides an in‐depth discussion from the national perspective and offers explanations from both quantitative and qualitative evidence. The study suggests that the implementation of the theory in egalitarian societies has been largely compromised with regard to meritocratic selection. Meanwhile, the theory relies on a veil of ignorance, for it assumes that people would have a unanimous perception regarding social status. In both respects, it is argued to be incompatible with the contemporary Chinese context. Thus a more comprehensive and flexible perspective is needed to identify functions of higher education in developing countries. 摘要: 工业自由主义提出教育是促进就业与提升社会地位的决定因素, 其理论对当代教育产生深远影响。然而, 当大学毕业文凭已不再是'金饭碗'的保证, 中国大学毕业们面临着逐渐暗淡的就业前景与日益渺茫的阶级跨越机会。因此, 本文就工业自由主义进行批判性探讨。通过引用研究数据, 结合量性与质性证据, 本文从国家层面进行深度探讨。本文提出, 工业自由主义与精英教育相左, 同时, 由于此理论搭建于人们对于社会地位的一致认知的假定, 其论证受 "无知之幕"矇昧。本研究旨在说明工业自由主义难以解释当代中国高等教育的困境, 并呼吁制定更全面理论, 采用更灵活的视角来了解发展中国家的高等教育模式。